The creation of hope in patients with lung cancer. (September 2014) - Salander, Pär; Bergknut, Mirjam; Henriksson, Roger
Abstract Background. Lung cancer is associated with biomedical and psychological symptoms as well as a generally poor prognosis. When healthcare staff communicate with lung cancer patients it is essential that they consider the patients' own views of the situation to avoid putting unnecessary strain upon the patients' shoulders. The purpose of the present study is to better understand how a group of patients with lung cancer reflects upon their new life situation after diagnosis and primary treatment. Method. Fifteen patients with non-small cell lung cancer were consecutively included and, where possible, repeatedly interviewed during the course of the disease process. The 29 interviews were conducted in a thematically structured narrative form that facilitated a dialog between the interviewer and the patient. The interviews covered experiences with health care, living an everyday life, and thoughts about the future. Findings and reflections. By focusing on how the patients more or less preconsciously elaborated mentally with their vulnerable situation, it was possible to detect different mental manoeuvres that they used as a way of creating hope. The patients distanced themselves from their disease, relied on a feeling of a sound body, idealised treatment possibilities, relied on healthy behaviour, focused on a concrete project, found that they were better off than others, and took solace in the fact that there were patients who had successfully managed the disease. Discussion. The patients were not passive victims in the face of their diagnosis, but were actively trying to find ways of looking at their despairing situation in a positive light. A creative process for psychological survival had thus been initiated by the patients. We suggest that acknowledging this process should be the starting point from which physicians can engage in hope work with their patients.